Analisis Hubungan Kualitas Pelayanan Dengan Tingkat Kepuasan Pasien Rawat Inap Di Rumah Sakit - Marhawati M (PT.Mantaya Idea Batara, 2022)
Service quality shows the level of perfection of health services in generating patient satisfaction. RSUD Haji Makassar is one of the government hospitals in South Sulawesi trying to provide good health services to the community, but there are still some complaints about the health services provided by the hospital. This study aims to determine the relationship between service quality and satisfaction level of inpatients at Haji Makassar Hospital. This type of research is a quantitative study with a cross sectional study approach . The population in this study were inpatients at Haji Makassar Hospital as many as 15,119 people. The sampling technique in this study used proportional random sampling with a total sample of 100 people. Data analysis was performed by univariate, bivariate with chi-square test. The results showed that there was a relationship between assurance (p value 0.026), empathy (p value 0.010) and responsiveness (p value 0.005 ) with the level of satisfaction of inpatients in RSUD Haji Makassar. It is recommended to the hospital to increase the responsiveness of health workers, especially by responding quickly to all patient complaints, both requested and unsolicited, providing suggestion boxes and following up on suggestions given by patients and immediately evaluating patient complaints.